International Conference on Health, Safety and Environment in Oil and Gas Exploration and Production 2012
DOI: 10.2118/157287-ms
|View full text |Cite
|
Sign up to set email alerts
|

Angola Biodiversity of Bathyal Sea Bottoms

Abstract: At the request of TOTAL E&P Angola (TEPA), before developing oil and gas activity, independent contractors carried out seven environmental baseline studies between 1998 and 2009 on bathyal blocks 17 and 32 located off the coast of Angola. With this aim, biological analysis were done on seabed samples at depths ranging between 682 and 2630 m, and 515 benthic macrofaunal taxa from eleven phyla were discovered. The relative dominance on richness taxonomic and abundance was observed on Polychaetes, but referring t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“…Depth-related patterns in the fauna of the Angolan margin appear to be typical, as in other areas (Carney, 2005), potentially related to transition zones between overlapping faunal components. The sediment-dwelling macrofauna in Angola show a similar mid-bathyal peak in abundance and species diversity (Cazes et al, 2012) to that found here. There was also high turnover with depth reported in the Angolan fishes, for example in Rajidae (Compagno and Ebert, 2009) and virtually no overlap (only the hagfish Myxine ios) in fishes collected at shallower below 800 m (277 species) (Tweddle and Anderson, 2008) compared to deeper (1297-2453 m) areas (Jamieson et al, 2017).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Depth-related patterns in the fauna of the Angolan margin appear to be typical, as in other areas (Carney, 2005), potentially related to transition zones between overlapping faunal components. The sediment-dwelling macrofauna in Angola show a similar mid-bathyal peak in abundance and species diversity (Cazes et al, 2012) to that found here. There was also high turnover with depth reported in the Angolan fishes, for example in Rajidae (Compagno and Ebert, 2009) and virtually no overlap (only the hagfish Myxine ios) in fishes collected at shallower below 800 m (277 species) (Tweddle and Anderson, 2008) compared to deeper (1297-2453 m) areas (Jamieson et al, 2017).…”
Section: Discussionsupporting
confidence: 79%
“…These studies have mostly focussed on chemosynthetic systems in the deep bathyal (Sibuet and Olu-LeRoy, 2002;Sibuet and Vangriesheim, 2009) and abyssal (Sen et al, 2017) or deepwater coral reefs on the upper slope (Le Guilloux et al, 2009). Less scientific attention has been directed towards the bathyal (200 -2000 m) depths of the margin, although this area has been the subject of many environmental assessments by the oil industry (Cazes et al, 2012). Access to the region through oil company activities has permitted some scientific investigations on the scavenging fishes in Block 18 and 31 (Jamieson et al, 2017) and on communities associated with asphalt mounds in Block 31 (Jones et al, 2014).…”
Section: Study Sitementioning
confidence: 99%